(untitled) (Philology, 2026)
In the following article has been made a research about the up-to-date issues concerning the linguistics, especially the part for the foreign language teaching in The Republic of Lebanon. A short flashback of the language teaching during the ages has been made. The main accent is focused on the preparing of a systematized analysis about the foreign language education during the last 50 years. Initially it has been characterized as bilingual but swiftly it became trilingual. In the context of the research has been examined the model of the gradual emergence of the English language as the primary choice of the first foreign language at secondary and university level.